Women of World Mythology and Folklore: A Poetic Re-imagining of Cultural Stories and Figures - Alblas, Elizabeth Jane (2023)
This thesis focuses on uncovering stories concerning female figures from world mythology and folklore. The creative component of my thesis, the poetry collection The Island Witch, explores, interprets, and reassesses myths, legends, and folktales from around the world through a feminist lens, interrogating themes of female agency, marginalisation, sexual assault, transformation, voicelessness, and ecofeminism, amongst others.